Achievements and perspectives in Chinese hamster ovary host cell engineering. (June 2015) - Xu, Ningning; Ma, Chao; Sun, Wendy; Wu, Youling; Liu, X Margaret
Intense efforts in bioprocessing development have been made to improve the production of Chinese Hamster Ovary-based biopharmaceuticals. However, lacking an efficient host cell has hampered therapeutic protein production. This article reviews means by which biopharmaceutical production can be improved via cell engineering. We first discuss the traditional and recently developed strategies to improve protein productivity through regulating cell growth and facilitating cell line construction, increase protein quality by upregulating the post-translational modifications and enhance production stability through targeting integration and chromatin remodeling. New cell engineering technologies, such as miRNA, CRISPR/Cas and synthetic promoter, are then reviewed. The application of advanced 'omics to reinforce a fundamental understanding of cellular metabolism and physiology is also described. Finally, rational cell engineering facilitated with 'omics technologies is presented.